The Landscape of MET Exon 14 Skipping Mutations in Patients With Lung Cancer Identified by Next-Generation Sequencing - Jia Liao, MD; Song Wu, MD; Yi Min, MD; Yiran Li, MD; Yuanhang Nie, MD; Quwen Chen, MD; Zhiliang Mao, MD; Qinglan Zong, MS; Ning Gao, MS; Ding Zhang, PhD; Weiquan Liang, MD (JTO Clinical and Research Reports, 2025)
Introduction: MET exon 14 (METex14) skipping mutations are observed in approximately 0.9% to 4% of patients with NSCLC. This study aimed to compare the detection rates of METex14 skipping in Chinese patients with lung cancer using DNA-based next-generation sequencing (NGS) with capture-based library construction and synchronous DNA-based and RNA-based NGS with amplicon-based library construction. Methods: A total of 11,330 tissue samples from 11,330 Chinese patients with lung cancer were included in the study to confirm the presence of METex14 skipping. Simultaneously, MET immunohistochemistry testing was performed on 30 patients. Results: The highest detection rate of METex14 skipping was observed in the synchronous DNA and RNA-based NGS with amplicon-based library construction, reaching 2.20%. A total of 45 different variants leading to METex14 skipping were detected at the DNA level. These variants were widely distributed across a 197–base pair DNA sequence. In the overall population, the incidence of METex14 skipping was significantly higher in individuals aged 60 years and above (p < 0.0001) and needle biopsy samples (p < 0.0001) and reported no significant association with gender and tumor location. A positive correlation was observed between microsatellite instability–high and METex14 skipping (p < 0.0001). Conclusions: The mutations causing METex14 skipping exhibit diversity in terms of variant types and are widely distributed across various genomic regions. Synchronous DNA-based and RNA-based NGS is considered the optimal method for detecting METex14 skipping. Furthermore, METex14 skipping is enriched in specific populations, including individuals aged 60 years and above, with advanced-stage disease and a microsatellite instability-high status.